Developing Rubric for Argumentative Writing Assessment Based on Multidimensional Approach - Paris, Atika Salman; Lustiyantie, Ninuk; Murtadho, Fathiaty; Rosyidi, Ahmad Zuhri; Suryadi, Hendra (LPPM Institut Pendidikan Nusantara Global, 2025)
This study developed a multidimensional rubric for assessing argumentative writing in English as a Foreign Language (EFL) context by integrating cognitive, metacognitive, affective, and socio-cultural dimensions. The rubric was designed in response to the limitations of traditional assessment tools that tend to focus on surface-level features, often neglecting essential aspects such as writer stance, planning, audience awareness, and contextual relevance. Employing a Research and Development (R&D) methodology, the study followed several stages: a needs analysis, literature review, initial rubric design, expert validation, and a small-scale implementation with undergraduate EFL students. The trial results demonstrated that the rubric effectively captured variations in writing performance across dimensions and supported a more nuanced understanding of students’ strengths and challenges. Students showed stronger performance in cognitive aspects such as argument structure and reasoning, while affective and socio-cultural awareness remained areas for pedagogical improvement. Feedback from both learners and instructors confirmed the rubric’s clarity, practicality, and potential to guide instruction and formative feedback. The study concludes that the rubric addresses critical gaps in current assessment practices and offers a comprehensive framework for supporting students’ development as reflective and context-aware academic writers. Future research is encouraged to validate the rubric in broader contexts, integrate it into digital platforms, and explore its impact on long-term writing growth.